Competent and deficient provision of childbirth services: a descriptive observational study assessing the quality of intrapartum care in two provinces of the Democratic Republic of the Congo - Brenner, Stephan; Madhavan, Supriya; Nseya, Céline Kanionga; Sese, Claude; Fink, Günther; Shapira, Gil (BMC health services research, 2022)
A majority of women in the Democratic Republic of the Congo (DRC) give birth in a health facility, but maternal and newborn mortality remains high. In rural areas, the quality of facility-based delivery care is often low. This study examines clinical quality of intrapartum care in two provinces of the DRC.